Leprosy in children under 15 years of age in a municipality in northeastern Brazil: evolutionary aspects from 2003 to 2015 - Pedro Martins Lima Neto; Antônio Rafael da Silva; Leonardo Hunaldo dos Santos; Raina Jansen Cutrim Propp Lima; Pedro Luiz Tauil; Eloísa da Graça do Rosário Gonçalves (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION The Integrated Program of Leprosy Control was initiated in 2003 in the municipality of Buriticupu, Maranhão, Brazil, an area considered hyperendemic for leprosy. Here, we present the evolution of the indicators of leprosy within the established period in children aged <15 years. METHODS: This is a descriptive study based on an active search for cases and spontaneous healthcare demand for leprosy, with an evolutionary analysis of the detection coefficient of new cases. We considered individuals aged <15 years diagnosed with leprosy from January 2003 to December 2015. To evaluate the factors associated with clinical and operational forms, Chi-square, Fisher’s exact, or Fisher-Freeman-Halton tests were performed. RESULTS A total of 61 new cases were detected (6.9% of the total leprosy cases diagnosed in the municipality during the study period), and the majority was found in males (62.3%). The most frequent operational classification was paucibacillary (67.2%), and this association increased with age. The tuberculoid clinical form was the most prevalent in both sexes and in the age range of 10 to <15 years. There was a reduction in the detection coefficient from 21.84/100,000 inhabitants in 2003 to 2.79/100,000 in 2015. CONCLUSIONS Despite the progress in the control of leprosy, this historical series shows that it is necessary to strengthen educational measures and implement control actions, so that the disease ceases to be a public health problem in the population aged <15 years.